The nexus of electricity consumption and economic growth in Gulf Cooperation Council economies: evidence from non-stationary panel data methods. Issue 1 (2nd January 2019) - Al-Mulali, Usama; Tang, Chor Foon; Tan, Bee Wah; Ozturk, Ilhan
ABSTRACT: This paper investigates the electricity-growth nexus of Gulf Cooperation Council (GCC) member countries from 1980 to 2014. To achieve the goal of this research, both panel cointegration and causality approaches are utilised to examine the long-term and causal relationships between variables. Empirical results confirm the presence of cointegration between variables. Moreover, this study finds that electricity consumption affects the long-term economic growth. Given that GCC member countries are energy-dependent economies, policies that aim to conserve energy consumption may jeopardise economic growth.